If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x = 12x + -8 + 1 Reorder the terms: -3x = -8 + 1 + 12x Combine like terms: -8 + 1 = -7 -3x = -7 + 12x Solving -3x = -7 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -3x + -12x = -7 + 12x + -12x Combine like terms: -3x + -12x = -15x -15x = -7 + 12x + -12x Combine like terms: 12x + -12x = 0 -15x = -7 + 0 -15x = -7 Divide each side by '-15'. x = 0.4666666667 Simplifying x = 0.4666666667
| 3=-0.1x+1 | | 45=-0.1x+1 | | 300x-0.04=500x+0.18 | | -3x=x+-8+1 | | 35=w^2+3w | | (z^2/3)(z^1/4) | | 5wsquared=17 | | 2(x-3)+8x=-36 | | x^2+7x+3=-7 | | X+4=5(4x-2) | | Y=-0.1(420)+1 | | 8(u+2)-4u=-24 | | X-9=-6+-5 | | -25=4(w-8)+3w | | Y=-0.1(600)+1 | | 9/2x=60 | | 34=8(y+5)-6y | | 0.2x+25=9 | | m^2-10m+10=14 | | [5n+9]+17=4 | | 4x+17=x-19 | | r^3+8=0 | | 7p^2=-6p+3 | | Y=-0.1(45)+1 | | 16a+8b= | | 2x^2-6x+9=340 | | Y=2+4.5x | | -3x^4+16x^3-27x^2=0 | | y=4.5x+2 | | Y=-22.5x-1 | | -c+11=2.4+x | | log(2x)+log(3x)=log(96) |